(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article presents a clinical and diagnostic analysis of a patient with atherothrombotic ischemic stroke in 100 patients. During the study, the relationship between patients’ age, gender, stroke severity (NIHSS), and MRI/CT and EEG indicators was studied. The results showed that the size and location of the stroke foci are directly correlated with the degree of neurological deficit (r = 0.71). It was also statistically confirmed that the risk of re-stroke increased with age (p≈ 0.045).